Right ventricular myocardial work: proof-of-concept for the assessment of pressure-strain loops of patients with pre-capillary pulmonary hypertension - Bárbara Lacerda Teixeira; Francisco Albuquerque; Raquel Santos; André Ferreira; Ricardo Carvalheiro; João Reis; Luis Almeida Morais; Tânia Mano; Pedro Rio; Ana Teresa Timoteo; Rui Cruz Ferreira; Ana Galrinho (Cardiovascular Ultrasound)
Abstract Background Right ventricular myocardial work (RVMW) assessed by transthoracic echocardiography allows to study the right ventricular (RV) function using RV pressure-strain loops. The assessment of these novel indexes of RVMW has not yet been exten sively studied, namely in pre-capillary pulmonary hypertension (PH) population. Objectives to evaluate the relationship between RVMW and invasive indices of right heart catheterization (RHC) in a cohort of patients with group I and group IV PH and to compare with a control group without PH. Methods A prospective registry of pre-capillary PH patients was used and compared with a control group without PH. In both groups, patients underwent same day RHC and echocardiographic assessment. Dedicated software for left ventricle myocardial work was used for the RV. RV global work index (RVGWI) was calculated as the area of the RV pressure-strain loops. From RVGWI, RV global constructive work (RVGCW), RV global wasted work (RVGWW), and RV global work efficiency (RVGWE) were estimated. Results 25 pts were included: 17 pts with PH were compared with 8 pts without PH. RVGWI, RVGCW and RVGWW were significantly higher in PH patients than in controls (p < 0,05), while RVGWE was significantly lower (p < 0,05). Significant correlations were found between mean pulmonary artery pressure, cardiac index, venous oxygen saturation, NT-proBNP and RVGCW, RVGWW and RVGWE; between pulmonary vascular resistance, cardiac output, right ventricular stroke work and RVGWI, RVGCW, RVGWW and RVGWE; between stroke volume and RVGWW and RVGWE; between pulmonary artery pulsatility index and RVGWI, RVGCW and RVGWW; between RA pressure and RVGWE. Conclusions Patients with pre-capillary PH present significantly higher RVGWI, RVGCW and RVGWW and lower RVGWE than patients without PH. Echocardiographic RVMW-derived indexes show significant correlation with invasive measurements and NT-proBNP. Larger studies are needed to assess the prognostic value of these novel indexes. Graphical Abstract